Efisiensi Penyisihan Chemical Oxygen Demand (COD) Limbah Cair Pabrik Sagu Menggunakan Bioreaktor Hibrid Anaerob Dua Tahap Dengan Variabel Laju Pembebanan Organik - Sartunus, Phivi Andriza; Ahmad, Adrianto; Syarfi, Syarfi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Sago industry has the potential to pollute the environment. This is because the concentration of COD contained in the sago industry environment quality standard that exceeds 55,000 mg / L. One way to lower the COD concentration is by using a hybrid anaerobic bioreactor two stages. The purpose of this study was to remove COD and determine the highest COD removal efficiency in wastewater treatment sago tunak Volume working conditions hybrid anaerobic bioreactor two stages used in this study was 10 L to 20 L the first stage bioreactor and the second stage in the bioreactor with variations of organic loading rate is 27.50 kgCOD / m3hari the first bioreactor and organic loading rate of 7.86 kgCOD / m3hari; 11 kgCOD / m3hari; 18.33 kgCOD / m3hari on the second stage bioreactor. Each organic loading rate is operated until steady state based on the data obtained COD. The results showed that most of COD removal efficiency was obtained in the operation of the organic loading rate of 27.50 kgCOD / m3hari amounted to 87.88% in the first stage bioreactor and organic loading rate of 7.86 kgCOD / m3hari amounted to 93.94% in the second stage bioreactor. The system of hybrid anaerobic bioreactor two stages mediated phase of this stone can be used as a technology that is used for treating wastewater effectively and efficiently sago.Keywords: anaerobic bioreactor hybrid, COD, sago wastewater, two stages.